A New Technique for Research on Wound Healing through Extraction of Mandibular Lower Incisors in Wistar Rats - Khoswanto, Christian (European Journal of Dentistry, 2019)
Objective The aim of this study was to explain a new technique for research on wound healing through extraction of mandibular lower incisors in Wistar rats.Materials and Methods Fifty Wistar rats were used from studies using the experimental animal to investigate the effects of wound healing drugs on alveolar bone. The mandibular incisors of the Wistar rats were extracted using a special modified bein and special pulling pliers under general anesthesia. The tooth socket after extraction was closed using a 5.0 suture nylon needle.Results The results of this technique used in this extraction showed 2% incisor tooth fracture and 3% bleeding, and that all fractured teeth could be removed properly, and bleeding could be stopped after suturing.Conclusion The new techniques we use can be useful for research on mucosal and alveolar bone healing, specifically finding new types of drugs to accelerate wound healing after alveolar bone post extraction.
Keywords: tooth extraction; mandibular incisors; alveolar bone healing